PERANCANGAN SISTEM INFORMASI PELAYANAN RESUME MEDIS DEMI MENUNJANG KLAIM BERKAS BPJS MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI RUMAH SAKIT GIGI DAN MULUT - Wiranata, Muhammad Renaldy (Jurnal Infokes, 2022)
This study aims to design and build a medical resume service information system to support BPJS files using Microsoft Visual Studio 2010 at Rumah Sakit Khusus Gigi dan Mulut Kota Bandung. A medical resume is a summary of the whole time care and treatment of patients carried out by the involved healthcare workers. This medical resume will be used as a request for one of BPJS hospital requirements. The use of information technology at this time must continue to grow to create quality information in hospitals. The design method used is descriptive qualitative analysis with data collection methods using observation techniques and software development methods using Waterfall method through the stages of analysis, requirements, system design, code, and implementation. The medical resume information system for BPJS claims at Rumah Sakit Khusus Gigi dan Mulut Kota Bandung is not yet computerized and is still done by hand, making it less efficient. Therefore, we need a more efficient information system to make it easier for medical record officers to check the completeness of medical records. If there is an unclear medical record, the medical record officers can immediately hand it back to the doctor in charge to complete it again. With this information system, it is hoped that it will make it easier for the medical record officers to check the completeness of medical records quickly and efficiently so that BPJS claim processes are not hampered. Keywords: BPJS, Microsoft Visual Studio 2010, Completeness of Medical Resume, Information System, Waterfall.